Determining adrenocortical activity as a measure of stress in domestic pig (Sus scrofa domesticus) based on salivary and faecal analysis - Fasina, Folorunso Oludayo (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.